Osteoporosis in women in menopause/postmenopause: what to do? - E. V. Kulchavenya (Медицинский совет, 2021)
An analytical review of domestic and foreign literature on the problem of osteoporosis was performed, and the principles of the approach to diagnosis and treatment of this disease are described.The probability of vertebral fracture should be assumed if there is a history of growth loss of 4 cm or more, the appearance of kyphosis in patients who received long-term therapy with glucocorticoids, with bone mineral density (BMD) less than 2.5 points In the treatment of patients with osteoporosis at the initial stage there is a tendency to limit oneself to non-drug measures, advising to change lifestyle and diet, to increase intake of vitamin D and calcium with food, to optimize physical activity. However, the main place in the prevention and treatment of osteoporosis in postmenopausal women is occupied by medication therapy, which can reduce the risk of fractures by 70%: bisphosphonates, drugs derived from parathyroid hormone, denosumab and selective estrogen receptor modulators. It is advisable to start therapy with oral bisphosphonates in most cases. They are powerful inhibitors of bone resorption and act by reducing the activity of osteoclasts and increasing their apoptosis. In 2020, the patent protection period of the main original bisphosphonates expired and generics of Russian production appeared: Rezoviva (ibandronic acid 3 mg for intravenous injection once every 3 months) and Osteostatix (zoledronic acid 5 mg 100 ml solution for intravenous drip once a year). After 3–5 years of bisphosphonate treatment, treatment should be reconsidered. The risk of recurrent fractures should be reassessed after the injury occurs. The risk of new fractures increases in patients who stop treatment. Study results have recommended ibandronate as a first-line drug in women with postmenopausal osteoporosis. Studies comparing intermittent intravenous ibandronate administration with daily oral treatment in women with postmenopausal osteoporosis allowed to recommend intravenous ibandronate at a dose of 3 mg every 3 months as the preferred therapy.